Dermoscopy in Selected Latin American Countries: A Preliminary Look into Current Trends and Future Opportunities Among Dermatology Residency Programs - Mariana Perez; Natalie Williams; Alejandra Avila; Renato Bakos; Flavia Bittencourt; Blanca Carlos-Ortega; Laura Garzona; Alejandra Larre-Borges; Cristian Naverrete-Dechent; Victor Pinos; Gabriel Salerni; Jackie Shum-Tien; et al. (Mattioli1885, 2023)
Introduction: Dermoscopy is a useful technique that aids in early detection of skin cancer by increasing diagnostic accuracy with adequate training. However, dermoscopy is not uniformly taught to residents worldwide. Dermoscopy training in Latin American dermatology residency programs has not been explored. Objectives: To assess current dermoscopy training among dermatology residency programs in Latin America (e.g. training modalities, preferred/most effective modalities per residents, diseases/pathologies taught). Methods: Cross-sectional survey distributed via email between March and May 2021. Chief residents from Argentina, Brazil, Colombia, Costa Rica, Chile, Ecuador, Guatemala, Mexico, Panama, and Uruguay were invited to participate. Results: 81 chief residents completed the questionnaire (81/126, 64.2%). 72% of programs had an established dermoscopy curriculum, with dedicated hours of training varying greatly by program. Institutions commonly utilized sessions with "unknown" dermoscopy images and direct teaching by experts in the clinical setting as supplements to lectures, also described by residents as most effective. The most commonly taught methods included pattern analysis (74.1%), the two-step algorithm (61.7%), and the ABCD rule (59.3%). Almost all respondents reported desiring additional training during residency and believe that dermoscopy training should be a requirement to graduate from residency. Conclusion: This study highlights the current landscape in dermoscopy training among dermatology residency programs in Latin America, demonstrating room for improvement and standardization in dermoscopic education and training. Our results serve as a baseline reference and provide valuable information to guide future educational initiatives incorporating successful teaching strategies (e.g. spaced education/repetition, flipped classroom model) used in dermatology and other fields.